Caring and Communicating: Facilitators’ Manual The Interpersonal Relationship in Nursing - Morrison, Paul; Barnard, Philip (Macmillan Education UK, 1991)
A companion to the same authors' Caring and Communicating, which together offer a complete package to teacher and learner
Keywords: Nursing